A STUDY OF ELECTRICAL ENERGY EFFICIENCY BUILDING (Journal of Engineering and Health Sciences, 2019)
The objective of this study is to reduce energy handling costs by introducing electrical energy efficiency programs such as improving the efficiency of lighting, reducing the loss of internal energy transmission on power cables and replacing inefficient equipment with energy efficient products to reduce the cost of electricity. In this study, energy analysis and energy consumption inefficiencies have been determined by scheduling energy consumption and expenditure by referring to last year's monthly electricity spending statement for 3 years. Monitoring of power consumption is to calculate the changing values such as power factor values, and reactive energy using power monitoring meters. Data analysis reveals that the practice of energy efficiency program techniques can be implemented to ease the inefficient use of energy and the reduction in electricity costs.